Outcomes of Intravesical bacillus Calmette-Guérin in a Multiracial Cohort with Nonmuscle Invasive Bladder Cancer. Issue 1 (20th January 2021) - Barry, Emily; Agalliu, Ilir; Maiman, Richard; Shreck, Evan; Kovac, Evan; Aboumohamed, Ahmed; Sankin, Alexander
Abstract: Introduction: We sought to determine if outcomes of bacillus Calmette-Guérin therapy in patients with nonmuscle invasive bladder cancer vary by race. Methods: A retrospective chart review was conducted on 149 patients treated with bacillus Calmette-Guérin for intermediate and high risk nonmuscle invasive bladder cancer between 2001 and 2018, and who were followed for cancer recurrence through March 2019. The primary outcomes were disease-free survival, low grade disease-free survival, high grade disease-free survival and progression-free survival at 5 years. Kaplan-Meier survival curves stratified by race (African American vs nonAfrican American) were analyzed for all the above outcomes and multivariate Cox regression analyses were also performed to compare recurrence differences by race after adjusting for age, sex, initial stage and grade. Results: Of the 149 patients 37.6% were Caucasian, 24.8% were African American, 26.8% were Hispanic and 10.7% were of other/unknown race. Disease stage at initial presentation was 65.1% Ta, 34.9% T1 and 18.1% carcinoma in situ, respectively. African American patients (37) did not have evidence for worse outcomes vs nonAfrican American patients when considering disease-free survival (54.1% vs 65.7%, p=0.202), high grade disease-free survival (58.8% vs 71.7%, p=0.158) and progression-free survival (83.8% vs 92.6%, p=0.117) at 5 years. Multivariate analysis did not reveal statistically significant racial differences in recurrence or progression. Conclusions: African Americans with nonmuscle invasive bladder cancer did not have worse disease recurrence and progression after receiving intravesical bacillus Calmette-Guérin treatment. Although there did appear to be a trend towards worse oncologic outcomes in African Americans, larger studies are needed to validate this finding.